QUALITY MANAGEMENT IN THE SUPPLY CHAIN: ANALYTICAL APPROACHES AND FACTORS TO DETERMINE OPTIMAL QUALITY LEVELS - Shetty, Tushar (2015)
Quality has been identified as an important component for each and every business, irrespective of their size and type, and hence, quality affects each and every activity of an organization crucial for their success. Therefore, since recent times, almost every organization has identified the need of perceiving quality and its management across the supply chain. There are a number of factors affecting the maintenance and management of quality across supply chain. As the topic itself his highly diversified and has to be considered and understood from a number of perceptions that result in differentiating the perception about how quality can be modelled across the supply chain. The aim of this research is focused on studying the variables and approaches used for studying and modelling quality at the upstream levels along with the downstream levels within the chain of supply. Further ahead, for assessing quality, factors such as price, quality and value from the perspective of customers play a significant role. And hence, there is a need to understand these factors in context with quality management of supply chain. There will be collection of both, secondary and primary data. The secondary data will be collected from different articles referring to different facts and case studies related to the topic of the research. Further ahead, for the collection of primary data, there will be a need for conducting a survey. On completing the research, there will be identification of key findings. It will be identified that the approach that is used most significantly for the maintenance of quality across the operations and management of supply chain includes the management of total quality, seeking for the improvement of performance as well as quality across the operation.